Energy of Sitnikov’s restricted three body problem if the primaries are source of radiation and triaxial rigid bodies - Thapa, R. R. (BIBECHANA, 2014)
In this paper the joint effect of source of radiation and triaxial rigid body has been studied. The energy of Sitnikov’s restricted three body problem when primaries are sources of radiation and energy of Sitnikov’s restricted problem of three bodies when primaries are triaxial rigid bodies have been studied to calculate the joint effect. Equation of motion of the third body of infitesimal mass, if primaries are sources of radiation and triaxial rigid bodies, are calculated. DOI: http://dx.doi.org/10.3126/bibechana.v12i0.11707 BIBECHANA 12 (2015) 53-58